A Study on The Role of Hr in Developing on Effective Performance Management System - Pathan, Muskan Irfan; Tekade, Atul (Journal of Neonatal Surgery, 2025)
The role of Human Resources (HR) in developing an effective Performance Management System (PMS) is crucial for organizational success. A well-structured PMS not only enhances employee performance but also aligns individual goals with broader organizational objectives, driving productivity and engagement. This study explores the key responsibilities of HR professionals in designing, implementing, and continuously improving PMS. It examines the integration of HR strategies with performance management tools, such as goal setting, feedback mechanisms, appraisals, and development programs, to foster a high-performance culture. Additionally, the research highlights the importance of HR in creating transparent communication channels, ensuring fairness, and addressing employee concerns. By focusing on best practices, challenges, and evolving trends, this study underscores how HR can be a strategic partner in driving a results-oriented and employee-centric performance management framework. The findings suggest that HR’s proactive involvement is essential for maintaining a PMS that is dynamic, adaptable, and capable of meeting both individual and organizational needs.